2017
DOI: 10.14196/mjiri.31.35
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in Iranian cancer patients

Abstract: Background: The identification and management of unmet needs is an essential component of health care for the growing cancer patient population. Information about the prevalence of unmet need can help medical service planning/redesigning. Therefore, this study aimed to identify unmet needs in Iranian patients suffering from cancer. Methods: This cross-sectional correlational study was conducted on 650 cancer patients admitted to the major medical centers in Mashhad and Neyshabur by census sampling. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…57 Nevertheless, as in this study and many other studies, 56,58 cancer patients usually use factors such as survival time and cost to choose the appropriate treatment. In the study of Tabriz et al 28 as in our study, financial needs were the most important needs of patients.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…57 Nevertheless, as in this study and many other studies, 56,58 cancer patients usually use factors such as survival time and cost to choose the appropriate treatment. In the study of Tabriz et al 28 as in our study, financial needs were the most important needs of patients.…”
Section: Discussionsupporting
confidence: 52%
“…For this purpose, several studies using quantitative and qualitative approaches have identified the information needs of cancer patients. [28][29][30] So far, several cross-sectional survey studies have been conducted, which did not identify most of the unmet needs due to the limited number of questionnaire items. 21,28 As far as we know, the available evidence has not explained the needs of patients with advanced cancer in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the majority of the unmet supportive care needs have been demonstrated in the health and information as well as psychological and social support domains. 14 , 15 , 16 , 17 Also, in women with breast cancer, the highest perceived needs were observed in information and physical and daily life needs. 17 Survivors of colorectal cancer also prioritized work and financial concerns over unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Survivors of colorectal cancer also prioritized work and financial concerns over unmet needs. 14 Also, the highest unmet needs have been reported in young people, comorbidity, female gender, and higher stage of the disease. 14 , 15 , 17 The unmet needs can cause mental and physical disorders, causing excessive use of health services and increased costs of caring for these patients for the health system.…”
Section: Introductionmentioning
confidence: 99%